Komparasi Media Konvensional Dan Baru Dalam Partisipasi Masyarakat Pada Pembangunan Di Kota Batam - Ageng Rara Cindoswari; Michael Jibrael Rorong (Prosiding, 2022)
The aims of this research are (1). Describe the characteristics of users of the apekesah.batam.go.id website and the Hallo Batam program on Batam FM, (2). Describe the use of apekesah.batam.go.id and the Hallo Batam program on Batam FM on community participation in development in Batam City. This study uses a qualitative research method where the research subjects are users of the apekesah.go.id application and the listeners of the hallo batam program who are selected prupossively, while the object of research is the place of research which is located in Batam City. Data collection techniques using snowball techniques with research instruments using observation, in-depth interviews and documentation and data analysis techniques using Miles and Huberman. The results showed (1) Batam FM users who access the hallo broadcast program mostly on diversion and surveillance motives. Furthermore, the motive of the apekesah.go.id website user is the motive for using it to run away from administration. (2). In Batam FM media, the participation that appears is horizontal participation, informative participation, functional participation and interactive participation. As for the impact of the use and benefits of the apekesah.go.id website users, it is shown by the emergence of informative and functional participation only